Interpretation and discussion (Scottish Historical and Archaeological Internet Reports, 2004)
This chapter considers the significance of the site's location which offered shelter and varied resources. The evidence points to human activity in the mid 7th millennium BC. The nature of the Scottish Mesolithic in this period and the role of the site are considered in the context of the wider Mesolithic world.